What we can learn from the dynamics of the 1889 ‘Russian flu’ pandemic for the future trajectory of COVID‐19 - Harald Brüssow (Wiley, 2021)
Summary A study of the contemporary medical literature for patient symptoms from the so‐called ‘Russian flu’ pandemic from 1889 revealed clinical observations that resemble COVID‐19 (Brüssow and Brüssow, 2021, Microb Biotechnol). If one accepts the hypothesis that this pandemic was a prior coronavirus epidemic, the dynamics of the ‘Russian flu’ from 1889 might give us some ideas about the future trajectory of the COVID‐19 pandemic. The present report compiles and reviews the contemporary data published on the temporal and geographical spread of the ‘Russian flu’, its epidemic wave structure and possible later resurgence. The historical record of past pandemics might thus provide us not with predictions, but ‘retrodictions’ on possible future scenarios for the COVID‐19 pandemic.